2019
DOI: 10.1186/s13014-019-1346-5
|View full text |Cite
|
Sign up to set email alerts
|

Stereotactic body radiotherapy with periprostatic hydrogel spacer for localized prostate cancer: toxicity profile and early oncologic outcomes

Abstract: Background Multiple phase I-II clinical trials have reported on the efficacy and safety of prostate stereotactic body radiotherapy (SBRT) for the treatment of prostate cancer. However, few have reported outcomes for prostate SBRT using periprostatic hydrogel spacer (SpaceOAR; Augmenix). Herein, we report safety and efficacy outcomes from our institutional prostate SBRT experience with SpaceOAR placement. Methods Fifty men with low- or intermediate-risk prostate cancer t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
37
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 47 publications
1
37
0
Order By: Relevance
“…Given the strict OAR sparing employed in the UHF SBRT planning strategies presented, it is evident that physical optimisation of the patient's anatomy at each treatment session is critical to enabling maximal target coverage. The use of hydrogel rectal spacers to temporarily enlarge the perirectal space has been associated with low toxicity in the context of prostate SBRT [32,33]. Optimal bladder filling for MR-Linac prostate radiotherapy relies upon a careful balance between the presentation of a sufficiently full bladder to displace the small bowel superiorly and the patient's ability to comfortably hold their bladder for the duration of treatment [34].…”
Section: Discussionmentioning
confidence: 99%
“…Given the strict OAR sparing employed in the UHF SBRT planning strategies presented, it is evident that physical optimisation of the patient's anatomy at each treatment session is critical to enabling maximal target coverage. The use of hydrogel rectal spacers to temporarily enlarge the perirectal space has been associated with low toxicity in the context of prostate SBRT [32,33]. Optimal bladder filling for MR-Linac prostate radiotherapy relies upon a careful balance between the presentation of a sufficiently full bladder to displace the small bowel superiorly and the patient's ability to comfortably hold their bladder for the duration of treatment [34].…”
Section: Discussionmentioning
confidence: 99%
“…The radiotherapy model for malignancy has transformed from conventional fraction radiotherapy (CFRT) to hypofractionated radiotherapy, which is now considered to be a new and highly effective mode of radiation therapy [1,2]. Stereotactic body radiotherapy (SBRT) and stereotactic radiosurgery are common procedures in hypofractionated radiotherapy, especially SBRT, which is widely performed for lung cancer, colorectal cancer, liver cancer, and prostate cancer, and shows considerable improvement in the radiotherapeutic outcomes [3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, in pelvic radiation therapy, a hydrogel spacer is used to decrease the rectum dose [6][7][8][9]. In de nitive radiation therapy for prostate cancer, SpaceOAR, a hydrogel spacer, is widely used to decrease irradiated dose and toxicity of rectum [10][11]. A prospective randomized study revealed that insertion of SpaceOAR signi cantly reduced the rectum dose and toxicity, and improved bowel/urinary quality of life [12][13][14].…”
Section: Introductionmentioning
confidence: 99%